The Subordination of The Queen in the Narrative Lampahan Juměněngipun Nata Dewi Kancana Wungu, an Episode of Langěndriya Manuscript - Nurmalia Habibah; Sharifah Hanidar (POETIKA, 2022)
Lampahan Juměněngipun Nata Dewi Kancana Wungu (LJNDKW) is a fragment of the legend of Damarwulan. It presents Kancana Wungu, a royal female figure who is represented in a more superordinate position than most of female characters in stories revolving around Javanese court life. The primary objectives of this study are: firstly, to explore the reason why this form of narrative becomes paradoxical and secondly, to find the meaning of it within its historical context. In order to achieve a more profound understanding of the narrative, a review of the positioning of women will be based on theories proposed by Sylvia Walby. By applying philological methods in collecting and providing readable narrative, this study then finds its interpretation of the narrative that “superordinate” position of the seemingly empowered queen is a form of segregation.